ANALYSIS OF QUANTITATIVE TRAITS OF MULTIVOLTINE SILKWORM, BOMBYX MORI L. (LEPIDOPTERA : BOMBYCIDAE) IN VARIED ENVIRONMENTS - GHOSH, B.; CHATTOPADHYAY, S.; RAO, PR. T.; DAS, S.K.; ROY, G.C.; SEN, S.K.; SINHA, S.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1993)
The quantitative performance of 10 evolved multivoltine silkworm breeds of Bombyx mori L. were studied under varied environmental condition to evaluate different quantitative traits. Statistical analysis (ANOVA) revealed that the overall performance of ABS, O yellow (Oval), NJB(Y), M2 and BCs (C) were better and may be utilised through hybridization.